Artificial Intelligence: Analysis and evaluation of technology - Liendo Arévalo, Milner David (2023)
The incorporation of technology to various sectors such as education, agriculture, medicine, and public and private entities has allowed the virtualization of various knowledge improvement strategies. For this reason, new projects have been evidenced such as self-development areas, platforms for mobile devices, robots, intelligent systems, virtual assistants and artificialintelligence, etc. These formats are an example of technological innovation aimed at developing diverse and beneficial educational formats, facilitating the digital transformation that drives innovation. Artificial intelligence has a variety of uses in society and is making great strides in new technologies like blockchain. By far, these are the most innovative and powerful strategies for designing architectures that provide security and reliability in massive data processing. The objective of this research is to determine a general perspective of the architecture used in traditional distributed systems using artificialintelligence tools that apply systematic mapping methodologies.